2012
DOI: 10.1021/om300401t
|View full text |Cite
|
Sign up to set email alerts
|

Amino-Acrylamido Carbenes: Modulating Carbene Reactivity via Decoration with an α,β-Unsaturated Carbonyl Moiety

Abstract: Two 6-methoxy-4-oxo-1,3-diaryl-3,4-dihydropyrimidinium salts (2a and 2b) have been prepared as precursors to novel amino-acrylamido carbenes. Treatment of 2a (where the aryl groups are mesityl groups) with one equivalent of sodium hexamethyldisilazide in aromatic hydrocarbons affords the persistent amino-acrylamido carbene 3a, which has been characterized spectroscopically. This novel carbene has been trapped with Ir(I) transition metal fragments as well as electrophilic carbon disulfide and nucleophilic isocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0
1

Year Published

2013
2013
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 48 publications
3
20
0
1
Order By: Relevance
“…[22] Characteristically, such a value is approaching the chemical shift measured for the related O-methyl-substituted amino-acrylamidocarbene (d = 257.2 ppm) reported by Hudnall and coworkers. [29] Moreover, the splitting of the 1 H and 13 C NMR signals is in agreement with a loss of symmetry in the heterocyclic ring, revealing that the silyl group is not shuttled between the two oxygen atoms, at least on the NMR timescale.…”
Section: Nhcmentioning
confidence: 62%
See 2 more Smart Citations
“…[22] Characteristically, such a value is approaching the chemical shift measured for the related O-methyl-substituted amino-acrylamidocarbene (d = 257.2 ppm) reported by Hudnall and coworkers. [29] Moreover, the splitting of the 1 H and 13 C NMR signals is in agreement with a loss of symmetry in the heterocyclic ring, revealing that the silyl group is not shuttled between the two oxygen atoms, at least on the NMR timescale.…”
Section: Nhcmentioning
confidence: 62%
“…These include the standard imidazol-2-ylidene IMes (2), its saturated imidazolin-2-ylidene SIMes (3), Bertrands "anti-Bredt" NHC 4, and the two more closely related neutral NHCs of [1]·Li, namely the diamidocarbene 5, and the amino-acrylamidocarbene 6. [29] The two orbitals playing a major role on the reactivity of a carbene are the in-plane, non-bonding occupied lone-pair of the carbon atom C1 (n s C1 ) and the vacant antibonding, ptype orbital centered on this carbon atom (2p p * C1 ). They generally constitute the HOMO and LUMO frontier orbitals of the free carbene.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bielawski and co‐workers reported that the six‐membered diamidocarbene (DAC) I was more electrophilic compared to typical NHCs (Figure 1), and favored NH and CH bond activation, reversibly fixing CO, coupling to isonitriles, and [2+1] cycloaddition of olefins, aldehydes, alkynes, and nitriles 4. The five‐memebered DAC II , reported by the groups of Bielawski4h and Ganter,5ac and the six‐membered amino‐acrylamido carbene III , reported by Hudnall and co‐workers,6a also display similar electrophilic properties. We envision that decorating NHCs with a conjugated backbone containing an α,β‐unsaturated carbonyl moiety would provide the NHC with additional stability and exhibit unprecedented electronic properties, thereby showing distinct reactivity behavior.…”
Section: Methodsmentioning
confidence: 84%
“…The spectra indicatedt hat the newly formed species was the betaine 7 formed by formal loss of am ethyl cation from 16,w hich was subsequently transferred to the nucleophilic DMSO molecule resultingi nt he formation of the well-known cation Me(CD 3 ) 2 SO + .Ar elated slow demethylation was also observed by Hudnall and co-workers for their amino-acrylamido carbene precursor. [26] Thus, the triazolium salt 16 is obviously ag ood electrophilic methylating agent. To confirm this, 16 wast reated with as eries of N-nucleophiles such as triethylamine, methylimidazole, pyridinea nd DABCO, which were all cleanly converted to the corresponding N-methylated cationic derivatives( dicationic in the case of DABCO) while 16 was converted backt o7.H owever,w en ever observed am ethyl transfer from Ot ot he N-atom resulting in the formationo fc ation 20.F urthermore, it should be noted that this N-methyl derivative 20 did not show any alkylating reactivity at all.…”
Section: Carbazide-based Nhcsmentioning
confidence: 99%